Investigating academic dishonesty and its relationship with moral competence and professional identity of nursing students: a cross-sectional study - Leila Homayouni; Azam Zare; Zahra Padam; Armin Fereidouni (BMC, 2024)
Abstract Background Academic dishonesty as a fundamental challenge in adherence of ethical principles in providing care to patients has caused concern to the scientific community of nurses. In addition, positive professional identity and high moral competence are important for nurses to perform multiple care roles in high quality care of patients. The purpose of the present study is of investigating academic dishonesty and its relationship with moral competence and professional identity of master's and PhD nursing students. Methods This descriptive-analytical study was conducted by census method on 65 master's and PhD nursing students in Shiraz University of Medical Sciences, Iran in 2023. Data collection tools included 4 questionnaires (Demographic information, Academic Dishonesty Scale (DAS), Nurses' moral competence and Professional Identity Scale for Nursing Students (PISNS)). Data collection was done within 2 months. Descriptive and inferential analyzes including independent t-test, Pearson correlation coefficient and linear regression were used to analyze the data. The collected data were analyzed by SPSS.V.22 software. P-value less than 0.05 was considered significant. Results The average age of 65 participants was 31.5 ± 5.61 years. The majority of the participants in this study were women 48 (73.8%). There is a significant and negative correlation between academic dishonesty and moral competence (r=-0.260, P-value = 0.036). There is no significant correlation between academic dishonesty and professional identity (r = 0.154, P-value = 0.22). Also, a significant positive correlation was found between moral competence and professional identity (r = 0.294, P-value = 0.018). Conclusion Therefore, considering that the fact that students have a great impact on patient care, Researchers suggest that educational institutions should prevent the increase of academic dishonesty among students by establishing new rules and regulations.